Hubungan penggunaan nasogastric tube dengan kejadian pneumonia pada pasien stroke akut dengan disfagia - Eva Rahmi Halim; Yuneldi Anwar; Puji Pinta O. Sinurat (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background : Aspiration pneumonia is the most important acute complication of stroke related dysphagia. Tube feeding is usually recommended as an effective and safe way to supply nutrition in stroke patients with dysphagia. On the cointains, many patients on continued to aspirate eventhough the used the nasogastric tube.The purpose of this study was to confirm that there werethe is correlation between nasogastric tube usege and incidence of pneumonia in acute stroke patient with dysphagia. Methods : This cross sectional study observed 60 acute stroke patients with dysphagia consist, 30 patiens using tube feeding and 30 were not using tube feeding, who stayed in Adam Malik General Hospital. Patients who admitted with pneumonia or other pulmonary infection or decreased level of conciussness were excluded. Patients were follow up in acute phase and pneumonia was diagnosed based on Center for Disease Control Criteria that were adopted by Indonesia Association of Lung Doctors.Results : In 30 acute stroke group patients with dysphagia who used nasogastric tube mean age is of 59 years old, 13(43.3%) females and 17(56.7%) males. While the other group who not do use nasogastric tube tube feeding were 30 acute stroke patients the mean age of 54 years old, 16(53.3%) males and 14(46.7%) females. There was no significant association with very weak correlation between Nasogastric tube usedwith pneumonia ( p=0591, r=0.063).Conclusion: Nasogastric Tube using does not have a significant with very weak correlation to the occurance of pneumonia. Keywords : nasogastric tube; pneumonia; dysphagia